Intrabody Targeting HIF-1α Mediates Transcriptional Downregulation of Target Genes Related to Solid Tumors - Yaozhong Hu (MDPI AG, 2021)
Uncontrolled growth of solid tumors will result in a hallmark hypoxic condition, whereby the key transcriptional regulator of hypoxia inducible factor-1α (HIF-1α) will be stabilized to activate the transcription of target genes that are responsible for the metabolism, proliferation, and metastasis of tumor cells. Targeting and inhibiting the transcriptional activity of HIF-1 may provide an interesting strategy for cancer therapy. In the present study, an immune library and a synthetic library were constructed for the phage display selection of Nbs against recombinant PAS B domain protein (rPasB) of HIF-1α. After panning and screening, seven different nanobodies (Nbs) were selected, of which five were confirmed via immunoprecipitation to target the native HIF-1α subunit. The inhibitory effect of the selected Nbs on HIF-1 induced activation of target genes has been evaluated after intracellular expression of these Nbs in HeLa cells. The dramatic inhibition of both intrabody formats on the expression of HIF-1-related target genes has been confirmed, which indicated the inhibitory efficacy of selected Nbs on the transcriptional activity of HIF-1.